Adaptive Laguerre filter for DS-CDMA multi-user communication system - Benjangkaprasert, C.; Inchan, T. (My University, 2010)
In this paper proposes a receiver for direct sequence-code division multiple access (DS-CDMA) multi-user communication system based on Laguerre filter and the recursive least squares (RLS) adaptive algorithm. Intersymbol interference (ISI) is usually caused by multipath propagation and the inherent non-linear frequency response of a channel. Therefore, the objective of this paper is to minimize the effects of ISI with a long impulse response environment based on the proposed receiver. Because of the stability of Laguerre structure is compromise between the finite impulse response (FIR) filter and infinite impulse response (IIR) filter. It can improve the bit error rate (BER) performance of the proposed receiver compared to the conventional FIR filter receiver. The simulation results show that the performances of the proposed receiver in terms of BER and the stability are better than does the conventional FIR filter receiver. ©2010 IEEE.
Keywords: Adaptive laguerre filter; DS-CDMA